The Draft Asset Confiscation Law in the Recovery of State Losses - Rifqi, Rifqi Dwi Bachtiar; Hidayatullah, Hidayatullah (Jurnal Ilmu Hukum Kyadiren, 2026)
Corruption constitutes an extraordinary crime that generates multidimensional harms and significantly undermines state finances. The effectiveness of anti-corruption efforts should be assessed not only through the punishment of offenders but also through the state’s capacity to recover losses by means of asset recovery mechanisms. This study examines efforts to recover state losses within the Indonesian criminal law system, analyzes the normative, structural, and practical obstacles encountered, and evaluates the urgency and relevance of the Asset Confiscation Bill as an alternative legal policy. Employing normative legal research, this study adopts statutory, conceptual, comparative, and case-based approaches. The findings indicate that state loss recovery mechanisms reliant on the criminal punishment of offenders remain suboptimal due to the complexity of corruption offenses and the limitations of existing legal instruments. Accordingly, the enactment of the Asset Confiscation Bill, grounded in an asset-based approach, represents a strategic measure to enhance the effectiveness of state loss recovery.